The Role of Financial Performance as a Mediating Variable in the Effect of Environmental Disclosure on Stock Performance in Mining and Energy Sector Companies Listed on the Indonesia Stock Exchange for the 2021–2024 Period - Sri Hartati Simamora; Arthur Simanjuntak; Rimky Mandala Simanjuntak; Merry Anna Napitupulu (Jurnal Ilmiah Accusi, 2026)
This study aims to analyze the effect of environmental disclosure on financial performance and stock performance, as well as to examine the role of financial performance as a mediating variable in the relationship between environmental disclosure and stock performance in mining and energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The study uses secondary data from annual reports, financial statements, and sustainability reports of 29 sample companies selected through purposive sampling, yielding 116 total observations. Environmental disclosure is measured using the Environmental Disclosure Index (EDI) based on 34 indicators from GRI 4 Environmental Category, financial performance is proxied by Return on Assets (ROA), and stock performance is measured using annual stock return. The analysis employs simple linear regression and mediation testing using the Baron & Kenny method through SPSS 26. The results show that: (1) environmental disclosure has a significant effect on financial performance, with R = 0.192, R² = 0.037 (3.7%), and sig. = 0.067; (2) financial performance has no significant effect on stock performance, with a regression coefficient of 0.722 and sig. = 0.239; (3) environmental disclosure has no significant effect on stock performance, with a regression coefficient of −0.292 and sig. = 0.346; and (4) financial performance is unable to mediate the effect of environmental disclosure on stock performance, as all mediation paths are statistically insignificant. These findings indicate that the Indonesian capital market has not yet optimally responded to environmental information in investment valuation for the mining and energy sectors, which may be attributed to the low level of investor ESG literacy, the dominance of external factors such as commodity price volatility and government policy, and the varying quality of environmental disclosures